Effect of Vegetable Marrow (Cucurbita pepo L. ) on Ice Cream Quality and Nutritive Value - Dagdemir, Elif (Asian Journal of Chemistry, 2011)
In the present study, the effect of adding vegetable marrow (VM) (control, 10, 15 and 20 % at concentrations) on the chemical, physico-chemical and sensory of ice cream mixes were investigated. Also concentrations of some major and minor minerals were determined in ice creams. The chemical composition of ice creams were affected with vegetable marrow addition significantly (p < 0.05). The addition of vegetable marrow increased the viscosity, first dripping time and complete melting time of ice cream samples, but decreased the overrun value depending to vegetable marrow concentration. While Ca and P contents of ice creams decreased by increasing of added vegetable marrow, the K content increased. The addition of vegetable marrow did not affect statistically concentrations of minor elements such as Mn, Ni. But Fe and Zn contents of ice creams significantly increased at 15 and 20 % concentrations. In the result of sensorial analysis the ice creams with 10 and 15 % of vegetable marrow concentration were preferred by the panelists. This work showed vegetable marrow might be used as new variety in ice cream production, especially at 10 and 15 % concentrations of vegetable marrow.